2017
DOI: 10.1088/1742-6596/891/1/012297
|View full text |Cite
|
Sign up to set email alerts
|

The study of the physical processes of low-temperature plasma formation and its effects on metal product surface

Abstract: Abstract. The article examines the physical processes associated with the formation and the impact of low-temperature plasma of combined discharge on the surface of metal products. It has been shown theoretically and experimentally that the propertiesgas discharge and the results of its action on the product surface depend significantly on the sign of the bias potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…In [17][18][19], it was shown that near the workpiece surface (figures 1(b) and 3) a plasma layer adjacent to it is formed, having a width of the order of the ampl itude of spatial electron oscillations x 0 , which turns out to be depleted of electrons due to their falling on the workpiece. As a result, part of the ion plasma core is exposed in this area, and an oscillating near-surface layer of a positive space charge is formed.…”
Section: Near-surface Layermentioning
confidence: 99%
See 4 more Smart Citations
“…In [17][18][19], it was shown that near the workpiece surface (figures 1(b) and 3) a plasma layer adjacent to it is formed, having a width of the order of the ampl itude of spatial electron oscillations x 0 , which turns out to be depleted of electrons due to their falling on the workpiece. As a result, part of the ion plasma core is exposed in this area, and an oscillating near-surface layer of a positive space charge is formed.…”
Section: Near-surface Layermentioning
confidence: 99%
“…Due to the small amplitude x 0 of plasma electron oscillations in the microwave field and, consequently, the small thickness of the arising surface layer d ≈ x 0 ∝ ω −2 with ϕ 0 = 0 the value U p ≈ 10-20 V [17,18], which is significantly less than the one characteristic of the high frequency discharge [19] where it reaches hundreds of volts.…”
Section: Near-surface Layermentioning
confidence: 99%
See 3 more Smart Citations